Acute Responses of Cardiac Biomarkers to Intermittent and Continuous Exercise Are Related to Age Difference but Not I/D Polymorphism in the ACE Gene - Falahati, Akram; Arazi, Hamid; Suzuki, Katsuhiko (Frontiers in Physiology, 2020)
Purpose The purpose of this study was to determine the (i) cardiac biomarker (cTnI and NT-proBNP) responses to moderate-intensity continuous exercise (MICE) and high-intensity interval exercise (HIIE) in the middle-aged and young groups, (ii) relationship of post-exercise cardiac biomarker release between these two age groups, and (iii) investigate whether insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme (ACE) gene is associated with predisposition to cardiac damage after exercise in Iranian men. Methods We examined cTnI and NT-proBNP in 29 middle-aged (54.5 ± 4.6 years) and 28 young (22.7 ± 4.2 years) soccer players before and after HIIE and MICE running tests. Results The middle-aged soccer players had higher baseline cTnI (0.015 ± 0.007 ng/ml vs. 0.010 ± 0.006 ng/ml; P = 0.01) and NT-proBNP (30.7 ± 13.6 ng/L vs. 18.4 ± 8.3 ng/L; P < 0.001) values compared with the young group. The changes with exercise (ΔcTnI: 13 vs. 11 ng/ml and ΔNT-proBNP: 18 vs. 11 ng/L) were also higher in the middle-aged group. No subject exceeded the upper reference limit for cTnI and NT-proBNP. Considering three ACE genotypes, the mean cTnI and NT-proBNP values of middle-aged and young groups did not show any significant difference. Conclusion Marked differences in baseline and post-exercise cTnI and NT-proBNP values were observed, which were related to age differences but not to ACE genotypes.